Fluorescence and bioluminescence imaging of the intestinal colonization of Enterococcus mundtii ST4SA and Lactobacillus plantarum 423 in mice infected with Listeria monocytogenes EGde - Van Zyl, Winschau Fayghan (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.